A STUDY ON CLINICOETIOLOGY AND OUTCOME IN A PATIENT WITH ACUTE PANCREATITIS - VALLURU SIVARAMAKRISHNA; PURUSHOTHAMG; YAMALA ANAND BABU; PADALA ADITYA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Acute pancreatitis (AP) is a common problem in medical practice. Mild AP recovers spontaneously within 1 week. Whereas high-grade AP patients suffer with severe complications such as necrosis and finally landing organ failure. The prognosis in these cases is very poor. This study was conducted to examine the clinical features, causative factors, and consequences of AP. Methods: This study was conducted in the Department of general surgery, S.V.R.R.G.G.H, Sri Venkateswara Medical College, Tirupati, after taking Institutional Ethical Committee from March 2021 to March 2023. 100 cases are taken for study. Results: Age group of patients included in this study was 18–70 years. The mean age of presentation is noted in this study was 38–86 years. Alcohol consumption is the most common causative factor identified in this study which is about 62%. Most of the cases presented with pain abdomen (90%) followed by vomiting (77%). Other clinical manifestations are abdominal distention (24%) and Jaundice (10%). Conclusion: Alcohol is the most common etiology being identified of about 62% of cases followed by gallstones 30%. The most common presenting complaints were abdominal pain and vomiting. The combination of serum amylase and serum lipase provided high sensitivity (95%) for the diagnosis of AP. Computed tomography was a non-invasive method of diagnosing and imaging complications.